Erosive Effects of Different Kinds of Beverages on the Enamel of the Extracted Teeth, Treated and Untreated by Fluoride Varnish - Ashar Hussain, Areeba Laghari, Asad Baloch, Mowaffaq Abdullmomen Al Absi, Muhammad Siddique Qazi, Aisha Mehboob, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fluoride varnish is often used to stop the irreparable damage caused by enamel erosion from acidic drinks, which is becoming a greater oral health problem. Objective: To evaluate the erosive effects of various beverages on enamel microhardness of extracted teeth, treated and untreated with fluoride varnish. Methodology: In this randomized experimental investigation, conducted over a period of six months from July 2021 to December 2021, 50 healthy permanent teeth that had been removed were split evenly between two groups: those that had fluoride varnish treatment and those that did not. Five subgroups (n=5) were created from each group and subjected to Coca-Cola, coffee, tea, milk, and sports drinks. Four times a day for seven days, teeth were submerged in 10 milliliters of the designated beverage for five minutes each time. They were then washed with deionized water and kept in fake saliva in between exposures. A Vickers microhardness tester was used to assess the surface microhardness before and after exposure. Scanning electron microscopy (SEM) was used to examine the surface morphology. Paired and independent t-tests with a 95% confidence interval were used for statistical analysis. Results: Coca-Cola showed the most enamel degradation, with both the treated and untreated groups showing substantial decreases in microhardness (p < 0.05). Significant erosion was also produced by Sports Drink. Milk had no discernible erosive impact, whereas tea and coffee caused a mild but statistically significant weakening of the enamel. Although fluoride varnish decreased the loss of enamel hardness, it was unable to totally stop erosion brought on by acidic drinks. Conclusion: Fluoride varnish offers some but not enough protection, and acidic drinks drastically weaken enamel. Milk is still non-erosive and may provide protection. Keywords: Enamel erosion, fluoride varnish, acidic beverages, microhardness, Coca-Cola, sports drink, scanning electron microscopy.